Answer:
x=3
Step-by-step explanation:
Answer:
25
Step-by-step explanation:
it's because 5 is squared so 5x5 is 25 and x squared
Answer:
(3)(x+7)(x-1)
Step-by-step explanation:
3x^2+18x-21
Let's start by taking 3 out of the equation.
3(x^2+6x-7)
Now, when we factor, we need to find two numbers that add up to 6 and multiply to -7.
The numbers would be 7 and -1.
So the factored form of this would be:
(3)(x+7)(x-1)
Hello
the equation is y = ax+b
a the slop a = 4
y = 4x+b
the line <span>passes through (3, -10) : -10 = 6(3)+b
b = -28
</span>the equation is y = 6x-28
1a) f(x) = I x+2 I. This is a piece-wise graph ( V form)
x = 0 →f(x) =2 (intercept y-axis)
x = -2→f(x) = 0 (intercept x-axis)
x = -3→f(x) = 1 (don't forget this is in absolute numbers)
x = -4→f(x) = 2 (don't forget this is in absolute numbers)
Now you can graph the V graph
1b) Translation: x to shift (-3) units and y remains the same, then
f(x-3) = I x - 3 + 2 I = I x-1 I
the V graph will shift one unit to the right, keeping the same y. Proof:
f(x) = I x-1 I . Intercept x-axis when I x-1 I = 0, so x= 1